Maternal mortality in pregnant women with positive SARS-CoV-2 antibodies and severe preeclampsia. Report of 3 cases - Collantes Cubas, Jorge Arturo (2020)
Maternal mortality from COVID-19 is rare in developed countries, but its association with other obstetric complications increases the risk. It is also associated with fetal death. Postpartum women are at risk of thrombosis that increases with COVID-19 coagulopathy. Comorbidities such as obesity, diabetes, and hypertension increase the risk of death from COVID-19, and pregnant women have more complications during the third trimester than in the first trimester, with higher risk than nonpregnant women of entering the ICU and requiring mechanical ventilation. In this report, stroke, diabetes and intracerebral hemorrhage were the three causes of death described, all within the context of stillbirth, severe preeclampsia, eclampsia and/or HELLP syndrome.